1972
DOI: 10.1002/cber.19721050522
|View full text |Cite
|
Sign up to set email alerts
|

Acetylen‐Gold‐Komplexe

Abstract: Disubstituierte Acetylene R-C =C-R (R = CH3, CzH5, C&) bilden bei Temperaturen unter 0" mit Gold(1)-chlorid Komplexe des Typs (R-C =C-R) .AuCI, mit Gold(II1)-chlorid solche des Typs (R--C=C-R),.AU~CI~ (n = 1 oder 2). Der ,,Mischkomplex'6 (DMA)2. AuzC14 wurde mit Hilfe seines 197Au-MoI3bauer-Spektrums als komplexiertesGold (1)-Salz der Tetrachloro-goldsaure [(D MA)2. A d ] +[AuC14]-erkannt. Die bei der Darstellung dieses Komplexes aus iiberschiissigem Dimethylacetylen (DMA) eintretende halftige Reduktion des Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Several examples for this -mode of co-ordination to both gold(I) and gold(III) are known in the literature (6,7,8), some examples have even been characterized by X-ray crystal structure analyses (9,10). Here the C-C-bond length increases from 1.19 Å, a normal value for an alkyne, to 1.26 Å.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Several examples for this -mode of co-ordination to both gold(I) and gold(III) are known in the literature (6,7,8), some examples have even been characterized by X-ray crystal structure analyses (9,10). Here the C-C-bond length increases from 1.19 Å, a normal value for an alkyne, to 1.26 Å.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Early studies on reactions of acetylene derivatives with Gold(III) chloride report chlorination of the triple bond and reduction of at least some of the Au(III) to Au(I) [24]. A behavior also observed in the hydrochlorination of acetylene with several gold catalysts [25].…”
Section: >80% >90%mentioning
confidence: 97%
“…(41) Albeit no examples of a stable bicyclo[3.2.0]hept-5-ene obtained by a metal-catalyzed reaction from a 1,6-enyne have been observed, interestingly, following earlier work done with PtCl 2 as catalyst, 171 it was found that the goldcatalyzed reaction of 1,6-ene-ynamides gives cyclobutanones (equation 42), 172 in a process that probably proceeds through unstable bicyclic enamines. A remarkable cyclization of a 1,9-enyne (equation 43) to form a 10-membered ring has been disclosed.…”
Section: 170mentioning
confidence: 94%